Applying the wilson methodology to improve process management. Case. Engineering services company (2023)
Knowledge management and information flow analysis are vital elements that can improve an organization's operations. Therefore, in this paper, the Wilson methodology will be applied. By using the recommended management, it would imply a strategic alignment, guaranteeing that all processes with their respective information flow in the same direction within the company, meeting business objectives, and allowing adapting the use of different strategic analysis tools, in such a way that it provides a benefit adjusted to each process, with a greater sensitivity in all employees aimed at the continuous improvement of the company